The relationship between language learning motivation and attitude among science students: a case study of a private college student / Zakhwan Aunie Al-Haffizz Zakaria - Zakaria, Zakhwan Aunie Al-Haffizz (2014)
Attitude, motivation and Language Learning Strategies have an impact on the second language acquisition. Positive attitude and motivation can facilitate the learners to be creative in the learning process; this will cultivate the independent learning which translates to the learners' effort in acquiring the language. Many studies have been done to investigate the effect of attitude, motivation and Language Learning Strategies towards the students' achievement in acquiring English as a second language. Thus, this study is driven to by previous research findings that mentioned about the connection between attitude, motivation and Language Learning Strategies towards second language achievement. Five research questions were constructed to help achieve the aims of this study. And the research questions have been divided into two scopes, scope one: influence of extrinsic and intrinsic motivation in learning English: and scope two: relationship between attitudes and motivation. This is based on language learning strategies in learning English as second language. The quantitative data were obtained through the distribution of 80 questionnaires to PICOMS students, 70 questionnaires were returned and analysed. The results show that PICOMS students are more intrinsically motivated to acquire English as second language. As for future research, bigger samples should be used in order to ensure the results are applicable and can be generalize to a larger population. In addition, the results may be used for further improvement for English language acquisition.